Audience Matters: 'Civilization-Speak', Educational Discourses, and Balkan Nationalism, 1800–1840. (October 2018) - Tipei, Alex R.
This article tracks how political and intellectual leaders from south-eastern Europe used the concept of civilization, or a particular type of 'civilization-speak', from the end of the eighteenth century through the mid-nineteenth century. It compares and contrasts how they employed civilization-speak in different linguistic milieus – French, Modern Greek, and Romanian – and how they deployed it to further changing political aims during a period of political upheaval in the Balkans. It traces how civilization-speak served initially as a tool for extracting support from west European, especially French, patrons, and was later refashioned into a rhetorical instrument of nationalism. This study places the intellectual and political history of south-eastern Europe during the era in a pan-European context and adds nuance to discussions about the development of nationalism in the region.